2018
DOI: 10.1002/ccd.27522
|View full text |Cite
|
Sign up to set email alerts
|

Absorb bioresorbable vascular scaffold vs. everolimus‐eluting metallic stent in small vessel disease: A propensity matched analysis of COMPARE II, RAI, and MAASSTAD‐ABSORB studies

Abstract: In this propensity-matched analysis pooling SVD patients of three large prospective studies, incidence of composite device-related events was comparable between BVS and EES up to 2 years follow-up. However, higher rates of stent thrombosis were found in the BVS group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…In the era of bare metal stents (BMS) and first‐generation DES, a RVD ≤3 mm has often been used as cut‐off . However, in more recent years, as smaller stent diameters have become available, lower thresholds for RVD (e.g., <2.75 mm or ≤2.5 mm), have more frequently been used to define small vessel PCI . Consequently, for this study we used RVD ≤2.5 mm to define SV‐PCI .…”
Section: Discussionmentioning
confidence: 99%
“…In the era of bare metal stents (BMS) and first‐generation DES, a RVD ≤3 mm has often been used as cut‐off . However, in more recent years, as smaller stent diameters have become available, lower thresholds for RVD (e.g., <2.75 mm or ≤2.5 mm), have more frequently been used to define small vessel PCI . Consequently, for this study we used RVD ≤2.5 mm to define SV‐PCI .…”
Section: Discussionmentioning
confidence: 99%
“…The higher rates of MI mainly driven by periprocedural events may be explained by the larger extension of CAD and once again by the structural characteristics of the device, with consequent higher risk of small branch occlusion and distal embolization [21][22][23] . Finally, these studies reported a lower rate of ST especially when a carefully lesion selection and predefined implantation technique were performed [24][25][26] . As a matter of fact, Regazzoli et al demonstrated a very low incidence of TLF and ST at 4-year follow-up adopting a dedicated implantation strategy of BRS in a real-world cohort of patients with a high prevalence of complex lesions (69.4% of type B2 or C lesions; 10.3% of severe calcific lesions; 26.1% of bifurcations) 27 .…”
Section: Longer Follow-up In Complex Scenariosmentioning
confidence: 97%
“…From analysis of clinical data, it is learned that most of the ST happened within 6 months after BVS implantation and many ST would have not occurred if small vessels were excluded (3,4), pretreatment, sizing, post-dilation (PSP) techniques were applied (5), and longer dual-antiplatelet therapy (DAPT) regimen were followed (6,7). These learnings were confirmed by the Absorb BVS 5-year follow-up studies, which showed that starting from the third year, when the BVS has diminished, target lesion failure (TLF) and ST of BVS have lowered down to the levels of that of DES (8,9).…”
Section: Introductionmentioning
confidence: 99%